Desenvolvimento e avaliação da metodologia da problematização na formação de estudantes do ensino superior - Tagliari, Celi Perin (2020)
University graduates are deficient in certain basic skills required by organizations today, demonstrating that there is a gap between educational formation and the current demands of the market, forcing the educational institutions to adapt to these needs. Many of the new proposals for educational formation are based on active teaching and learning methodologies, giving priority to teaching by research, avoiding teaching by transmission. Active methodologies can contribute to the development of these skills and competencies required to professional market. This research proposed to develop a methodology to apply the Arc Method of Maguerez and to evaluate the effectiveness learning transversal skills effectiveness develop under student point of view. It was proposed to the students develop a project, in a Polymeric Systems class in a class of the Bachelor of Chemistry at UFSCar, where they should choose real problem and find possible solutions using skills not normally worked in a traditional methodologies as join theoretical with practical knowledge; studies from various sources and technical standards; research and teamwork. In this study was analyzed the motivation and participation of students in the teaching and learning process in Polymeric Systems class, the perceptions about their development, professional skills and the methodology applied. The results of this work show that students realized the importance of developing transversal skills and agree that the methodology used by most teachers in the class of the Bachelor of Chemistry does not contribute to its development.